2011
DOI: 10.1002/mop.26039
|View full text |Cite
|
Sign up to set email alerts
|

All optical half adder/subtractor using dark‐bright soliton conversion control

Abstract: We propose a new design of all‐optical circuit using microring and nanoring devices, in which the simultaneous operation of half adder/subtractor arithmetic can be formed by using the dark‐bright soliton conversion control within the system. The input logic “0” and “1” are performed by using dark and bright soliton pulses, respectively. By using the dark‐bright soliton conversion behavior with in the π/2 phase shift device (i.e., an optical coupler), the arithmetic unit can perform simultaneously at the drop‐ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The operation of a half adder/subtractor arithmetic using dark-bright soliton conversion control has been reported by Phongsanam et al [7]. Many designs for a single adder or adder with subtractor have been proposed using a semiconductor optical amplifier (SOA) and periodically-poled lithium niobate (PPLN) waveguide [8], a microring resonator [9], exploitation of four-wave mixing (FWM) in a SOA [10], a three-state system [11], a terahertz optical asymmetric demultiplexer (TOAD) [12], a single-slot waveguide [13], two SOAs [14], and an SOA assisted by an optical bandpass filter [15].…”
Section: Introductionmentioning
confidence: 90%
“…The operation of a half adder/subtractor arithmetic using dark-bright soliton conversion control has been reported by Phongsanam et al [7]. Many designs for a single adder or adder with subtractor have been proposed using a semiconductor optical amplifier (SOA) and periodically-poled lithium niobate (PPLN) waveguide [8], a microring resonator [9], exploitation of four-wave mixing (FWM) in a SOA [10], a three-state system [11], a terahertz optical asymmetric demultiplexer (TOAD) [12], a single-slot waveguide [13], two SOAs [14], and an SOA assisted by an optical bandpass filter [15].…”
Section: Introductionmentioning
confidence: 90%
“…The nonlinear optical pulse input and control fields at the input and add ports of the modified add-drop filter are formed by the nonlinear dark pulse (D) and nonlinear bright pulse (B), which are given by reference [18] as shown in equations (5) -(6), respectively.…”
Section: Operating Principle and The-orymentioning
confidence: 99%
“…All-optical binary adders using many optical designs, such as terahertz optical asymmetric demultiplexers (TOADs) [15] and ultrafast nonlinear interferometers [16], have been reported. An alloptical half adder using an SOA-assisted Sagnac interferometer has been suggested and demonstrated by several groups of researchers [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…A scheme for an ultrahigh-speed all-optical half adder based on four-wave mixing in SOAs has been demonstrated by Li et al [17]. The operation of a half adder/subtractor arithmetic using the darkbright soliton conversion control has been reported by Phongsanam et al [18]. Menezes et al have suggested all-optical half adder using the symmetric planar three-core non-linear directional coupler, operating with a short light pulse [19].…”
Section: Introductionmentioning
confidence: 99%